2018
DOI: 10.1007/s10620-018-5278-y
|View full text |Cite
|
Sign up to set email alerts
|

PNPLA3 Gene Polymorphisms in HCV/HIV-Coinfected Individuals

Abstract: The HRM method is an effective, rapid technique for characterizing PNPLA3 genotype. In those with HCV/HIV infection, nearly 40% carry gene polymorphisms associated with the development of NASH or ASH. Prospective studies should focus on this group to determine whether they represent a subset of HIV-infected persons at increased risk of fibrotic progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…While HCC development also reduced by DAA, HCV/HIV co-infected patients with advanced cirrhosis is still represent a risk group for this outcome, with the highest risk of HCC progression in DAA non-responders. Thus, the heterogenicity of these cirrhotic patients based on various co-morbidities, genetic polymorphism[87-89], late treatment initiation and altered response to treatment may affect the end-stage liver disease progression in coinfected patients.…”
Section: Hiv/hbv Co-infection-induced Liver Injurymentioning
confidence: 99%
“…While HCC development also reduced by DAA, HCV/HIV co-infected patients with advanced cirrhosis is still represent a risk group for this outcome, with the highest risk of HCC progression in DAA non-responders. Thus, the heterogenicity of these cirrhotic patients based on various co-morbidities, genetic polymorphism[87-89], late treatment initiation and altered response to treatment may affect the end-stage liver disease progression in coinfected patients.…”
Section: Hiv/hbv Co-infection-induced Liver Injurymentioning
confidence: 99%
“…More than fifty studies demonstrating that the PNPLA3 rs738409 G allele is a risk factor for non-alcoholic steatohepatitis (NASH), liver cirrhosis in NASH or alcoholic liver disease have been published in the past decade [511]. The same allele was also identified as a risk factor for liver fibrosis and cirrhosis in HCV-monoinfected individuals [1216] and in those with HCV/HIV coinfection [1720] and it also turned out to be a predisposing factor of hepatocellular carcinoma (HCC) [2124]. In a recent study, the increased risk of HCC and PNPLA3 G allele was found only in alcoholic liver disease, but not in non-alcoholic fatty liver disease or viral hepatitis B and C [25].…”
Section: Introductionmentioning
confidence: 99%
“…The methodology for determination of PNPLA3 SNPs, and its validation have been previously described [ 9 ]. Briefly, PBMCs (peripheral blood mononuclear cells) from the study participants were isolated from peripheral blood collected in CPTs (cell preparation tubes) (Becton Dickinson Co., Franklin Lakes, NJ, USA), according to the manufacturer’s directions.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, some antiviral medications may enhance risk of liver injury by a variety of mechanisms including weight gain with increased insulin resistance [ 6 , 7 ]. There are relatively limited data regarding the role of PNPLA3 single nucleotide polymorphisms (SNPs) in the development of steatosis, liver injury and fibrosis among those with HIV infection [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation